Possible Relevance of Receptor-Receptor Interactions between Viral- and Host-Coded Receptors for Viral-Induced Disease - Luigi F. Agnati; Giuseppina Leo; Susanna Genedani; Diego Guidolin; Nicola Andreoli; Kjell Fuxe (The Scientific World Journal)
It has been demonstrated that some viruses, such as the cytomegalovirus, code for G-protein coupled receptors not only to elude the immune system, but also to redirect cellular signaling in the receptor networks of the host cells. In view of the existence of receptor-receptor interactions, the hypothesis is introduced that these viral-coded receptors not only operate as constitutively active monomers, but also can affect other receptor function by interacting with receptors of the host cell. Furthermore, it is suggested that viruses could also insert not single receptors (monomers), but clusters of receptors (receptor mosaics), altering the cell metabolism in a profound way. The prevention of viral receptor-induced changes in host receptor networks may give rise to novel antiviral drugs that counteract viral-induced disease.